Implantação do cuidado farmacêutico em um serviço oncológico - Bonini, Maíra Bernardt (2023)
Pharmaceutical care can be carried out, in oncology practice, in an effective and reproducible way, through the provision of pharmaceutical clinical services, aiming at the rational use of medicines, in addition to the promotion, protection and recovery of health, as well as the prevention of health problems associated with cancer. However, there are few models and reports on the deployment and development of these pharmaceutical clinical services in the outpatient hospital setting for patients undergoing cancer treatment, with oral medications. The objective of this study was to propose a model for deployment clinical pharmaceutical services (SCF) in a hospital oncology unit. This is a descriptive, cross-sectional research with a qualitativequantitative approach, developed in the pharmacy of an Oncology Center (CO) of a hospital in the south of the country that is a regional reference in cancer treatment by the Unified Health System. SCF deployment included the discovery stages (search for theoretical-practical references and legislation applied to pharmaceutical care in oncology); exploration (application of validated and adapted data collection instruments to characterize the clinical team and outpatients); preparation (organization of tools necessary for implementation) and presupposed the testing, operation and sustainability stage (pilot test after deployment). As a result of the study, health, labor and professional legislation was found in the discovery that established the role of the clinical pharmacist, but there was little guidance for pharmacists who work in the care of outpatients. There was also a lack of experiences that addressed and discussed the SCF deployment process. During the exploration, the need to mobilize the CO team to understand the role of the clinical pharmacist was identified. It was identified that the majority of patients were women, not elderly, with breast cancer, using oral hormonal therapy (tamoxifen, anastrazole) and who demonstrated satisfaction with the care received by the team and confidence in the treatment they were receiving. In preparation, workflows were established for prescription, dispensing, education and pharmacotherapeutic monitoring activities and tools and training actions necessary for the deployment of the SCF were suggested. The testing, operation and sustainability stage, in turn, was not carried out. It was concluded that creating SCF is a major challenge. The methods and tools used must be adapted to the reality of each institution, considering management support, the care scenario, available resources and benefits for patients.